Risk Preference of Farmers and Technical Efficiency of Rice Farming in Flood-Prone Areas of East Java, Indonesia - Wenny, Mamilianti; Desy Cahyaning, Utami; Kelvin Angga, Pramadani (INTI International University, 2025)
Although there is an increase in studies about the research on the farmers’ preference against production risks and the technical efficiency of the rice farming business, the issue of natural disaster-prone areas in agricultural areas is not yet widely discussed. The agricultural sector’s dependence on nature is still high, so the study about the production risks and the technical efficiency of rice farming business is still interesting to discuss. This research aims to analyze the rice farmers’ risk preference and the technical efficiency level of rice production in the flood-prone areas. The Just and Pope approach is used to analyze the farmer’s preference towards the production risks, and the stochastic frontier analysis is used to study the technical efficiency level of rice farming. This research involved 240 farmers as the respondents in three regencies in East Java, namely Ngawi, Bojonegoro, and Pasuruan regencies. Interviews and questionnaires became the instruments used to collect the primary data. This research found that in Ngawi Regency, the farmers tend to have a risk-seeking behavior and are more efficient in production. This shows that the risk-seeker farmers tend to be efficient in doing the farming business. Based on the findings, it’s expected to be used as a consideration by the local government in offering incentive programs and increasing the farmers’ skills, focusing on technology and increasing the farmers’ managerial capacity.